Expanding the mutational spectrum associated to neural tube defects: Literature revision and description of novel VANGL1 mutations. Issue 1 (10th September 2014) - Merello, E.; Mascelli, S.; Raso, A.; Piatelli, G.; Consales, A.; Cama, A.; Kibar, Z.; Capra, V.; Marco, Patrizia De
Abstract : Background: Neural Tube Defects (NTD) are a common class of birth defects that occur in approximately 1 in 1000 live births. Both genetic and nongenetic factors are involved in the etiology of NTD. Planar cell polarity (PCP) genes plays a critical role in neural tube closure in model organisms. Studies in humans have identified nonsynonymous mutations in PCP pathway genes, including the VANGL genes, that may play a role as risk factors for NTD. Methods: Here, we present the results of VANGL1 and VANGL2 mutational screening in a series of 53 NTD patients and 27 couples with a previous NTD affected pregnancy. Results: We identified three heterozygous missense variants in VANGL1, p.Ala187Val, p.Asp389His, and p.Arg517His, that are absent in controls and predicted to be detrimental on the protein function and, thus, we expanded the mutational spectrum of VANGL1 in NTD cases. We did not identify any new variants having an evident pathogenic effect on protein function in VANGL2 . Moreover, we reviewed all the rare nonsynonymous or synonymous variants of VANGL1 and VANGL2 found in patients and controls so far published and re‐evaluated them for their pathogenic role by in silico prediction tools. Association tests were performed to demonstrate the enrichment of deleterious variants in reviewed cases versus controls from Exome Variant Server (EVS). Conclusion: We showed a significant ( p = 7.0E‐5) association between VANGL1 rare genetic variants, especially missense mutations, and NTDs risk. Birth Defects Research (Part A) 103:51–61, 2015. © 2014 Wiley Periodicals, Inc.